2006
DOI: 10.1097/01.pgp.0000209570.08716.b3
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Adenomyoma

Abstract: The aim of this study is to highlight the importance of diagnosing uterine adenomyoma and help in differentiating it from other sinister lesions. Adenomyoma of the uterus is a circumscribed nodular aggregate of benign endometrial glands surrounded by endometrial stroma with leiomyomatous smooth muscle bordering the endometrial stromal component. It may be located within the myometrium, or it may involve or originate in the endometrium and grow as a polyp. A retrospective analysis of 26 consecutive cases of ute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Typical adenomyomas are intramural, firm, and smooth-surfaced tumors [ 14 ]. They show gray-white surfaces and are well demarcated from the myometrium on cut sections, and their smooth muscle component shows hypertrophy but does not make nodular proliferation with collagen fibers [ 15 ]. However, we can also find a few previous case reports of adenomyoma with prominent cystic change extended to the pelvic cavity [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typical adenomyomas are intramural, firm, and smooth-surfaced tumors [ 14 ]. They show gray-white surfaces and are well demarcated from the myometrium on cut sections, and their smooth muscle component shows hypertrophy but does not make nodular proliferation with collagen fibers [ 15 ]. However, we can also find a few previous case reports of adenomyoma with prominent cystic change extended to the pelvic cavity [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of cases, the border between the lesion and the surrounding myometrium is not clear. Therefore, the term ‘adenomyoma’ may be interpreted as grossly circumscribed adenomyotic masses ( 4 ). Medical therapy for adenomyosis may be effective.…”
Section: Introductionmentioning
confidence: 99%
“…These tumors are rare and can be divided into typical and atypical types based on the histopathology. Histologically, typical polypoid adenomyomas have regular, benign, tubular endometrial glands within a benign appearing smooth muscle stroma and well-demarcated myometrial smooth muscle [4]. On the other hand, endometrial glands with varying degrees of atypia within a myofibromatous stroma are identified in atypical polypoid adenomas [5].…”
Section: Discussionmentioning
confidence: 99%